Impact of introducing flexibility in the Colombian transmission expansion planning. (15th August 2018) - Henao, Alvin; Sauma, Enzo; Gonzalez, Angel
Abstract: Power transmission expansion planning (TEP) is a process affected by uncertainty that requires a long-term vision to anticipate requirements of interconnections among generators and load centers. Flexibility is an alternative to cope with uncertainty that increases social welfare. This article seeks for estimating the value of this flexibility and interpreting its meaning in the Colombian power system. In order to keep this focus clear, we implement a well-known methodology of Real Options (RO) in a simplified version of the Colombian power system. Accordingly, we introduce flexibility using a simple strategy of adding new transmission lines and make a simple comparison with a robust approach, as the one currently used in Colombia. Our results show that introducing this flexibility in the Colombian TEP increases social welfare in around 35 million, which represents an upper bound for the additional investment costs incurred to provide this adapting ability to the power system. These results suggest the need for revising the current paradigm of robust approach to prepare future Colombian transmission plans. Highlights: The impact of introducing flexibility in the Colombian TEP is analyzed. Flexibility increases social welfare in the Colombian TEP. Making flexible a power system requires an extra-cost. An upper limit for this extra-cost is imposed by the flexibility value.